Rancang Bangun Media Pembelajaran Berbasis Game menggunakan RPG Maker MV - Rizaldi Bagus Jiwo; A Fadiah Aini (Sains Data Jurnal Studi Matematika dan Teknologi, 2023)
Game is something made with certain techniques and methods that can give pleasure or inner satisfaction. Game (RPG) is a game that has elements of a complex story and acting that makes one feel like a character in the game. This game is a game in the form of game software in the form of an RPG game using the RPG Maker MV software. This game is based on a true story that is currently happening, namely Covid-19. The research method used in making the RPG game is Rapid Application Development (RAD) where the research stages are in the form of re-quirements planning, design process, and implementation. Plan requirements to achieve a goal of an application or system and find out the information needs in order to achieve the requirements, then the design process includes the design process and make improvements if there are still design discrepancies between users and analysts, and the implementation stage where the programmer develops a design program that can be tested. From the results of this study, it is possible to create a covid-19 educational game entitled "Covid-19". With this game, players can understand the covid-19 disease and the symptoms of covid-19 and also how to overcome the disease.